Viruses Infecting Soybean and Molecular Characterization of Soybean Mosaic Virus Isolates in the Black Sea Region of Turkiye - Deligoz, Ilyas; Sevik, Mehmet A.; Yilmaz, Nazli D. Kutluk (Elsevier, 2025)
Many viruses are known to infect and damage soybean (Glycine max) around the world. To detect viruses and determine their incidence, surveys were conducted in soybean fields in Samsun province located in the northern part of T & uuml;rkiye for four consecutive years from 2014 to 2017. Soybean mosaic virus (SMV) and cucumber mosaic virus (CMV) were detected in soybeans after analyzing 444 leaf samples by enzyme linked immunosorbent assay (ELISA). SMV was the most prevalent virus, with an average of 13.9%, followed by CMV (3.6%), and SMV + CMV (0.9%) in this study. However, alfalfa mosaic virus (AMV), tobacco ringspot virus (TRSV), and tomato spotted wilt virus (TSWV) were not detected in any of the soybean samples tested. In this study, four SMV-infected samples were selected according to their location and the SMV isolates were molecularly analyzed based on P3 cistrons. Results showed that all SMV isolates were the same at the amino acid level in terms of P3 amino acid sequence when those isolates were compared. The BLAST analysis of the P3 cistron of the Turkish SB20, SC25, and STK1 isolates showed that they were most closely related to the German Salzlandkreis-2_17 isolate (99.71-99.62% nucleotide identity; 100% amino acid identity, respectively), while the other isolate, STR2, was more similar to the Iranian Ar33 and Lo3 isolates, the German Salzlandkreis-2_17, and the Dutch Summer Shell isolates (99.62% nucleotide identity; 100% amino acid identity, respectively). To our knowledge, this is the first report for SMV and CMV infection in soybean plants in the Black Sea Region and the first molecular characterization of SMV isolates in T & uuml;rkiye.
Sevik, Mehmet Ali/0000-0002-8895-7944; Deli̇göz, İlyas/0000-0003-3646-300X
Keywords: Glycine Max; ELISA; SMV; CMV; P3; Sequencing